Out-of-time-order-correlators in holographic EPR pairs - Shoichi Kawamoto; Da-Shin Lee; Chen-Pin Yeh (Journal of High Energy Physics)
Abstract In this note, we investigate the out-of-time-order correlators (OTOCs) for quantum fields in a holographic framework describing Einstein-Podolsky-Rosen (EPR) pairs. We compute the four-point and six-point OTOCs using the gravity dual, represented by the string worldsheet theory in Anti-de Sitter (AdS) space. These correlators quantify the rate at which information is scrambled, leading to the disentanglement of the EPR pair. We demonstrate consistency between two approaches for calculating OTOCs: the holographic influence functional on worldsheets perturbed by shock waves, and the worldsheet scattering in the eikonal approximation. We show that the OTOCs exhibit an initial phase of exponential growth, with six-point correlators indicating a marginally longer scrambling time compared to four-point correlators.